Stateczność Nieliniowych Drgań Wahadła Sprężystego z Ruchomym Punktem Zawieszenia - C. Broniarek; B. Radziszewski (Engineering Transactions)
The subject-matter of the present considerations is kinematically forced vibration of a pendulum with a concentrated mass attached to an arm made of a material, the rheological properties of which are described by the Voigt model. The motion of the pendulum is described by a set of two nonlinear ordinary differential equations with variable coefficients. In a few particular cases this analysis concerns also an indeformable arm. The influence of the parameters describing the physical properties of the arm on the stability regions of the motion is discussed.